2014
DOI: 10.1108/ijwbr-01-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Buying a product for an anticipated consumption situation

Abstract: Purpose – The purpose of this study is to measure the product involvement of wine buyers and to examine relationships with anticipated consumption situations, places and occasions combined with the buyer’s importance of various extrinsic product attributes. Design/methodology/approach – A survey is conducted with 147 wine buyers using structured self-administered questionnaires in a central city retail location in Australia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 46 publications
(65 reference statements)
5
10
0
Order By: Relevance
“…H2.1-H2.3 are accepted. Consistent with previous research (Bruwer et al , 2013; Hirche and Bruwer, 2014), occasions seem to be an important influencing factor and could explain the significantly higher ( p < 0.01) Sauvignon blanc purchase frequency, compared to the other varietals.…”
Section: Resultssupporting
confidence: 91%
“…H2.1-H2.3 are accepted. Consistent with previous research (Bruwer et al , 2013; Hirche and Bruwer, 2014), occasions seem to be an important influencing factor and could explain the significantly higher ( p < 0.01) Sauvignon blanc purchase frequency, compared to the other varietals.…”
Section: Resultssupporting
confidence: 91%
“…Regarding wine attribute preferences, this study found significant differences among involvement groups in terms of quality, region, taste, grape variety and international awards and medals which are in line with previous studies (Hollebeek et al , 2007; Hirche and Bruwer, 2014). However, price, packaging and brand did not differentiate the involvement groups.…”
Section: Discussionsupporting
confidence: 91%
“…These results go in line and endorse the belief that there is a higher concern about quality and social benefits when the wine is bought to offer or to be drank socially rather than when it is bought for self-consumption (Hall et al, 2001;Outreville and Desrochers, 2016;Boncinelli et al, 2019). Also, it also supports findings that show that the visual component of a bottle, in this case, the label, increases in importance for anticipated situations involving reference groups (Hirche and Bruwer, 2014), since it is expected that consumers will spend more time analysing the wines in those cases.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, desire is more important and leads to higher purchase levels if the wine is bought to be consumed alone that if it is to drink in a social environment. Such results bring a new light to how the perception of risk may act an enabler of certain purchases, in other words, one could say that if the risk of choosing a wine with less quality is taken from the equation, then individuals' are more willing to buy a bottle not because it has an award (which is frequently associated to higher quality and more important for occasions with a social environment) but because they are simply searching for a wine for their personal enjoyment (Hirche and Bruwer, 2014).…”
Section: Discussionmentioning
confidence: 99%